Intravascular Schistosoma mansoni Cleave the Host Immune and Hemostatic Signaling Molecule Sphingosine-1-Phosphate via Tegumental Alkaline Phosphatase - Elzoheiry, Manal; Da’dara, Akram A.; Bhardwaj, Rita; Wang, Qiang; Azab, Manar S.; El-Kholy, El-Saeed I.; El-Beshbishi, Samar N.; Skelly, Patrick J. (Frontiers in Immunology, 2018)
Schistosomes are intravascular parasitic platyhelminths that infect >200 million people globally. These long-lived parasites do not appear to provoke thrombus formation or overt inflammation around them in vivo. Proteins expressed at the host-parasite interface (such as Schistosoma mansoni alkaline phosphatase, SmAP) are likely key to these abilities. SmAP is a glycoprotein that cleaves the artificial substrate p-nitrophenyl phosphate in a reaction that requires Mg2+ and at an optimal pH of 9. SmAP additionally cleaves the nucleoside monophosphates AMP, CMP, GMP and TMP, all with a similar Km (~600-650 µM). Living adult worms, incubated in murine plasma for one hour, alter the plasma metabolome; a decrease in sphingosine-1-phosphate (S1P) is accompanied by an increase in the levels of its component parts - sphingosine and phosphate. To test the hypothesis that schistosomes can hydrolyze S1P (and not merely recruit or activate a host plasma enzyme with this function), living intravascular life-stage parasites were incubated with commercially obtained S1P and cleavage of S1P was detected. Parasites whose SmAP gene was suppressed using RNAi were impaired in their ability to cleave S1P compared to controls. In addition, recombinant SmAP was shown to be capable of hydrolyzing S1P. Since extracellular S1P plays key roles in controlling inflammation and platelet aggregation, we hypothesize that schistosome SmAP, by degrading S1P, can regulate the level of this bioactive lipid in the environment of the parasites to control these processes in the worm’s local environment. This is the first report of any parasite being able to cleave S1P.